Eksplorasi Pengaruh Kecemasan Sosial Terhadap Gaya Komunikasi Pada Mahasiswa: Pendekatan Grounded Theory - Almadina Rakhmaniar (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2023)
This study explored the impact of social anxiety on communication styles, academic and social performance, as well as strategies used to cope with this condition. The main findings show that social anxiety correlates with a tendency towards a passive communication style and the use of avoidance strategies. Individuals with social anxiety tend to avoid active participation in group discussions and opt for silence, which is influenced by feelings of inadequacy and fear of negative evaluation. Avoidance strategies, such as avoiding public communication situations, are used as coping mechanisms to reduce perceived anxiety. Social anxiety also had a significant impact on academic and social participation. Study participants reported decreased academic participation, such as fear of asking questions or participating in class discussions, which affected understanding of subject matter and academic performance. In addition, social anxiety often leads to social isolation, exacerbating loneliness and anxiety levels. Strategies used to cope with social anxiety include seeking social support from friends and family. This emotional support was shown to help individuals feel more comfortable and safe in social situations, reduce stress and These findings emphasize the importance of social support and interventions that promote social interaction to improve mental well-being and reduce the negative impact of social anxiety.